(untitled) (Bangladesh Journal of Child Health, 2018)
Background: Quantification of proteinuria is usually predicted upon 24-hour urine collection. Multiple factors influence urine collection and the rate of protein and creatinine excretion. A spot urine protein-creatinine (P-C) ratio has been shown over the years to be a reliable alternative to the 24-hour collection for detection and follow up of proteinuria. The objective of the study was to evaluate the accuracy of urine protein creatinine ratio (UP/UC) in a spot sample for quantitative measurement of proteinuria in comparison with 24 hours urinary protein excretion in children of nephrotic syndrome having normal Glomerular Filtration Rate (GFR). Methodology: This was a prospective study conducted in the department of paediatrics, Sir Salimullah Medical College & Mitford Hospital Dhaka over a period of six months from January 2003. Fifty cases of Nephrotic syndrome were included who were on initial attack and relapse cases noted down into the proforma with respect to history, examination and investigation. All the patients were advised regarding 24 hours urine collection. They were asked to give a 24 hours urine sample starting at 9.00 am for total protein excretion rate. A spot urine sample was obtained and urine protein/creatinine ratio was calculated. The data was analyzed by linear regression and by calculating the correlation coefficient between urinary protein/ creatinine ratio and 24-hour urinary protein. Results: Sample size was fifty. Urine total protein in a timed 24-hour sample of nephrotic syndrome patients was in the range of 300-3150mg/m2/hour with the mean value of 1725 mg/m2/hour. While as U(Pr/Cr) ratio ranged from 3.1-27.5 with the mean value of 15.2. A significant correlation was found between timed 24-hour urinary protein and UP/UC ratio (r=0.622, p=<.001.) Conclusions: Spot urine protein-creatinine ratio is highly reliable and rapid test for quantification of proteinuria in children with nephrotic syndrome. Bangladesh J Child Health 2018; VOL 42 (3) :108-111